Changes in soil chemical properties using Dichotomius satanas (Harold, 1867) (Coleoptera: Scarabaeidae: Scarabaeinae) in greenhouse conditions (Revista de Investigaciones Universidad del Quindío, 2010)
The aim of this study was to evaluate the activity of dung beetles Dichotomius satanas Harold 1867, fed on cattle and pig excrement, and its effect on soil nutrients of depleted soil nutrients. For this, we collected specimens of D. satanas with 432 pitfalltrapson three sites at the Quindío Department. For data analysis we used a factorial design randomized complete block in order to evaluate the effects: beetles (presence or absence) and type of dung (cattle and pigs), repeated 4 times. The soils treated with cattle and pig excrement showed a significant decrease in pH, C.I.C and the content of P, K, Ca, Mg, Zn and Mn. Whereas, soils treated with D. satanas and cattle and pig excrement were significant increases in pH, organic matter, .C.I.C and the content of P, K, Ca, Mg, Cu, Zn and Mn; addition to this, there was a significant decrease in the concentration of Fe. The P was one of the highest improvement (6 to 120 ppm) with the increasing of pig manure and beetles activity. This study showed that the activity of D. satanas significantly grows up the availability of nutrients in soil type andisol deteriorated, leading to a change in representative soil chemical properties in just 45 days.
Keywords: Dungbeetles; nutrients; dung